Boards of directors in SMEs: An empirical evidence of board task performance - T. Iturralde; A. Maseda; B. Arosa; R. García-Ramos (South African Journal of Business Management, 2016)
This paper seeks to provide a better understanding of what makes boards effective. We analyse the relationships between board demography and company performance and between working structures and board tasks in small and medium-sized enterprises (SMEs). We test our hypotheses on a sample of 307 Spanish SMEs. The main empirical result is the negative impact that the proportion of outside directors and the board size have on firm performance. We also find a negative impact of outsiders' presence and a positive impact of director tenure on the board's service role. Our analysis of the role of board control highlights the negative relationship between this variable and CEO tenure.
Keywords: 650